Indoxyl Acetate as a Substrate for Analysis of Lipase Activity - Valek, Tomas; Kostelnik, Adam; Valkova, Pavla; Pohanka, Miroslav (International journal of analytical chemistry, 2019)
Lipases play a crucial role in metabolism of microbes, fungi, plants, and animals, and in analytical chemistry, they are often used in detection of fats and triglycerides. Determination of lipase activity is also important in toxicology, when lipase activity can be both increased and decreased by organophosphates and other pesticides and in medicine for diagnosis of heart diseases. The standard method for lipase activity determination is based on cleaving ester bonds in lipase buffer containing Tween. Our aim was to find a method with faster and more sensitive response. It is known that acetylcholinesterase belongs to the same group of hydrolases enzymes as lipases and it cleaves indoxyl acetate, so we assume indoxyl acetate could report a similar reaction with lipase. Our method is based on indoxyl acetate as a substrate for lipase, where indoxyl acetate is cleaved by lipase to indoxyl and acetate moiety and blue indigo is created. The method was optimized for different times and amount of enzyme and compared with the standard Tween assay. The calibration curve measured in reaction time 20 minutes with 10 μl of lipase exhibited the best analytical parameters, and it showed Michaelis-Menten response with the Michaelis-Menten constant equal to 8.72 mmol/l. The indoxyl acetate-based method showed faster and more sensitive response than the standard method for lipase activity determination, so it has great potential in biosensor construction and it could be used in industry, medicine, toxicology, and common practice where the activity of lipases is need to be measured.